Black gold and frankincense : photographs of Southern Arabia by the early oil explorers 1947-1971 - Morton, Michael Quentin (Abu Dhabi - UAE National Archives, 2010)
When the author's father, Mike Morton, arrived with René Wetzel and Tony Altounyan in Aden at the start of their first expedition to southern Arabia in the autumn of 1947, they met Wilfred Thesiger, the great explorer, who was about to embark on his second crossing of the Empty Quarter. This is the starting point for Black Gold and Frankincense. The book contains some 200 colour and black and white photographs of the people of southern Arabia before the oil started to flow. In English and Arabic, it expands on the author's first book, In the Heart of the Desert, with photographs of local people in a variety of settings: in their villages, at water wells, working in salt mines, riding camels, dancing, attending weddings, or simply posing for the camera. For many of these subjects, this was the first time their photograph had been taken. The book also depicts the ancient mouments and artefacts that the geologists found on their journeys, and concludes with the advent of the oil age in the countries known today as Yemen, Oman and the UAE.
Keywords: Petroleum--Prospecting--Middle East--History